2010
DOI: 10.1177/1367493509359173
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and children’s perceptions of active video games: a focus group study

Abstract: Energy expenditure studies have shown that playing Active Video Games (AVGs) is positively associated with increases in heart rate and oxygen consumption. It is proposed that playing AVGs may be a useful means of addressing inactivity and obesity in children. This study explored children's and parents' perceptions of AVGs and the likely facilitators and barriers to sustained use of AVGs. Data were gathered using focus group interviews: seven with children, four with adults. Both children and parents reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 18 publications
4
38
0
3
Order By: Relevance
“…15,16 One reason for such low frequency of active game-play in the present population could be a preference for outdoor games and play as also favoured by 13-to-14 year-old New Zealand boys. 17 In the present study, children who consumed foods and/or drinks during active gaming reported a significantly longer play time in comparison to those who did not. The additional energy expended by active game-play could be counterbalanced by this EI.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…15,16 One reason for such low frequency of active game-play in the present population could be a preference for outdoor games and play as also favoured by 13-to-14 year-old New Zealand boys. 17 In the present study, children who consumed foods and/or drinks during active gaming reported a significantly longer play time in comparison to those who did not. The additional energy expended by active game-play could be counterbalanced by this EI.…”
Section: Discussionmentioning
confidence: 61%
“…The children had easy access to active gaming consoles and games at home, as do New Zealand children 17 and Canadian and Dutch adolescents. 14,15 As with the Canadian adolescents, the children preferred the Nintendo Wii™ console and Nintendo Wii™ Sports game compendium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could have been "contaminated" since participants did not perform the activity as they should have (Baranowski et al, 2012). Also, these results could be the consequence of small samples and short intervention periods, focus on the wrong type of learner or underprovided design intervention (e.g., Chung, Vanderbilt, & Soares, 2015;Dixon et al, 2010;Gao, Hannon, Newton, & Huang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, active games give children the opportunity to engage in an activity they like [46][47][48] in their own home while getting some exercise. An aspect that children like about active games is the suitability to play with friends.…”
Section: Pa/pimentioning
confidence: 99%